THE EFFORT TO INCREASE STUDENT LEARNING OUT COMES IN SUBJECT OF SCIENCE MATERIALS BETWEEN RELATIONSHIP LIVING THINGS AND ITS ENVIRONMENT THROUGH DEMONSTRATION METHOD USING IMAGE MEDIA IN CLASS IV UPTD. SD NEGERI NO. 190 KOTANOPAN KECAMATAN KOTANOPAN KABU - GUSTI SALAMAH (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This type of research is Classroom Action Research (CAR) using the Demonstration method using image media in learning which aims to determine the extent to which the use of this method can improve student learning outcomes on the subject of understanding the Human Skeleton in Class V UPTD. State Elementary School No. 190 Kotanopan, Kotanopan Subdistrict, Mandailing Natal Regency. The subjects of this study were students of Class V UPTD. State Elementary School No. 190 Kotanopan, Kotanopan Subdistrict, Mandailing Natal Regency with 24 students, 13 of whom are women and 11 are boys. Based on the results of the pre-cycle test, many students have not finished learning. Of the 21 students of Class IV UPTD. State Elementary School No. 190 Kotanopan, Kotanopan Subdistrict, Mandailing Natal Regency, only 6 students (25%) scored 70 and above (completed). While the other 18 students (75%) scored below 70 (not completed). For this reason, researchers feel the need for an effort to improve student learning outcomes in science learning by carrying out Learning Improvements through research. From the research carried out, it was found that there was an increase in learning outcomes after the action was carried out. In the first cycle, the percentage of student learning completeness was 54.2% and the score of class completeness was 62.5% with the lowest score of 50 and the best score of 80. In the second cycle, the percentage of student learning mastery was 100% and the score of class completeness was 87% with a score of 87%. the lowest was 70 and the best score was 90. There was an increase in students' science learning outcomes from cycle I to cycle II, for the percentage of student learning mastery there was an increase of 45.8% and the score of class completeness was 24.5%. Science learning activities of students in the first cycle was 62.4%, while in the second cycle it was 74.5%. There was an increase in student activity from cycle I to cycle II by 12.1%. The average value in the first cycle is 65 and in the second cycle it is 78.3. There was an increase in student activity from cycle I to cycle II by 12.1%. The average value in the first cycle is 65 and in the second cycle it is 78.3. There was an increase in the value of 13.3. Likewise, teacher activity in the first cycle was 76%, while in the second cycle it was 86%. an increase in teacher activity or performance by 10%. And in the end there is a significant influence between the demonstration learning model using image media on student learning outcomes, the higher the student's activity in learning, the higher the value of learning outcomes obtained.